100 most cited articles in urban green and open spaces: a bibliometric analysis - Rakhshandehroo, Mehdi; Mohd Yusof, Mohd Johari; Ebrahim, Nader Ale; Sharghi, Ali; Arabi, Roozbeh (Enviro Research Publishers, 2015)
Researchers have contributed significantly to the development of the subject of urban green and open spaces (UGOS) in both practical and fundamental aspects. As the number of citations indicates a paper and author’s competency, the online web of science (ISI) was browsed to identify the 100 most cited papers in the field of UGOS from 1980 to 2013. Papers were analyzed for authorship, journal sources, publishers, institutions, countries, year of publication, categories, and author keywords. The total number of citations was compared to the average number of citations per year. From 1105 UGOS papers returned, the maximum number of citations was 212. The top 100 most cited were published from 1988 to 2011, with the majority in 2007. A remarkable distinction was found in the comparison of total citations and average citations per year. As total linear trend indicates a significant growth in influential articles, urban green and open spaces are a developing subject in landscape and urban planning. This study gives an insight into the readership of UGOS by highlighting key papers.